Methylprednisolone is related to lower incidence of postoperative bleeding after flow diverter treatment for unruptured intracranial aneurysm - Dong, Linggen; Liu, Qingyuan; Chen, Xiheng; Zhang, Longhui; Wang, Jiejun; Peng, Qichen; Li, Jiangan; He, Hongwei; Liu, Peng; Lv, Ming (Frontiers in Aging Neuroscience, 2023)
Background and objectives: Regarding the anti-inflammatory effect, methylprednisolone is a candidate to prevent patients with unruptured intracranial aneurysms (UIAs) from postoperative bleeding (PB) after flow diverter (FD) treatment. This study aimed to investigate whether methylprednisolone is related to a lower incidence of PB after FD treatment for UIAs. Methods: This study retrospectively reviewed UIA patients receiving FD treatment between October 2015 and July 2021. All patients were observed until 72 hours after FD treatment. The patients receiving methylprednisolone (80mg, bid, for at least 24 hours) were considered as standard methylprednisolone treatment (SMT) users, other non-SMT users. The primary endpoint indicated the occurrence of PB, including subarachnoid hemorrhage, intracerebral hemorrhage, and ventricular bleeding, within 72 hours after FD treatment. This study compared the incidence of PB between SMT users and non-SMT users and investigated the protective effect of SMT on PB after FD treatment using the Cox regression model. Finally, after controlling the potential factors related to PB, we performed subgroup analysis to further confirm the protective effect of SMT on PB. Results: This study finally included 262 UIA patients receiving FD treatment. PB occurred in 11 patients (4.2%), and 116 patients (44.3%) received SMT postoperatively. The median time from the end of surgery to PB was 12.3 hours (range: 0.5-48.0 hours). The patients receiving SMT had a lower incidence of PB comparing with patients receiving non-SMT (1/115, 0.9% vs. 10/146, 6.8%, respectively; P=0.017). The multivariate Cox analysis demonstrated that SMT (HR, 0.12 [95%CI, 0.02-0.94], P = 0.044) users had a lower risk of PB postoperatively. After controlling the potential factors related to PB (i.e., gender, irregular shape, surgical methods [FD and FD + coil] and UIA sizes), the patients receiving SMT still had a lower cumulative incidence of PB, comparing with patients receiving non-SMT. Conclusion: SMT was correlated with the lower incidence of PB for patients receiving FD treatment and may be a potential method to prevent PB after the FD treatment.